The Effect of the Inquiry Learning Model on Junior High School Students’ Learning Achievement in Indonesian Language Subjects - Intan Anggriani; Randi Randi (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Indonesian language learning at the junior high school level still faces challenges, including low student achievement, often due to the use of teaching models that do not actively engage students. Therefore, it is necessary to implement a learning model that encourages student participation, such as the Inquiry Learning Model. Objective: This study aims to examine the effect of the Inquiry Learning Model on the achievement in Indonesian language learning of eighth-grade students at SMP Negeri 5 Bengkulu City. Method: The research employed a quasi-experimental design with an experimental and a control class. Data were collected through achievement tests, and analysis was conducted using SPSS version 27, including tests for normality and homogeneity, and hypothesis testing. Findings: The results showed that the experimental class increased from 57.40 to 83.20, while the control class increased from 58.80 to 72.60. The t-test results indicated a t-value of 4.520 with a significance level of 0.000, leading to the rejection of H₀ and acceptance of H₁. Conclusion: The Inquiry Learning Model has a significant effect on students’ achievement in Indonesian language learning. Contribution: This study provides empirical evidence and serves as a reference for teachers in implementing active, student-centered learning approaches.